The nondermatophyte molds: Emerging as leading cause of onychomycosis in south-east Rajasthan - K R Raghavendra; Devendra Yadav; Akshay Kumar; Mukul Sharma; Jitendra Bhuria; Anita E Chand (Wolters Kluwer Medknow Publications, 2015)
Background: Onychomycosis is a fungal disease of the nail apparatus caused by both dermatophytic and nondermatophytic strains. Treatment involves long duration antifungal therapy. However, long treatment duration without identifying the causative species may lead to resistance. Confirmation of diagnosis and speciation by culture before administering antifungal therapy is ideal. Aims: To study the clinical and epidemiological aspects of onychomycosis in Hadoti region (south-east Rajasthan) and identify various mycological strains and predisposing factors causing onychomycosis. Materials and Methods: A prospective study of clinically diagnosed cases of onychomycosis attending the outpatient Department of Dermatology in our institute conducted from June 2012 to May 2013. The clippings were subjected to potassium hydroxide (KOH) examination and culture in the appropriate medium. Results: A total of 150 cases were enrolled in our study. There were 110 males (73.33%) and 40 females (26.66%) and male to female ratio was 2.75:1. The total dystrophic onychomycosis was the most common presentation seen in the majority of cases (46%) followed by distal lateral subungual onychomycosis in 52 cases (34.6%), mixed onychomycosis in 16 cases (10.66%), superficial white onychomycosis in 11 cases (7.33%), and proximal subungual onychomycosis in 2 cases. None had the endonyx variant. Direct microscopic examination of the nail clipping mounted with 40% KOH demonstrated fungal elements in 83 (55.33%) cases. Rate of isolation of organisms by culture was 64%. Nondermatophytes were isolated in 53 (35.33%), dermatophytes in 28 (18.66%), and yeasts in 15 (10%) of cases. The most commonly isolated species was Aspergillus in 45 (30%) cases. Aspergillus flavus was more commonly isolated compared to Aspergillus niger. Conclusion: The nondermatophyte molds appear to be more common causative agents of onychomycosis compared to usual dermatophyte species in south-east Rajasthan. Our study re-emphasizes the importance of culture for diagnosis of onychomycosis in every suspected case prior to therapy.